Bolted Connection Design Recommendation of Nyatoh Hardwood for Retrofitting the Unreinforced Masonry Buildings - Xavier Langit, Ujan (Universiti Malasia Sarawak, 2023)
Referring to the design code of the Malaysian Timber Standard of MS544: Part 5: 2001, the design of timber bolted connections only considers the ductile failure mode. This is opposed to the agreed principle set by the international timber engineering community of timber design standards. The principle states that the design code should be able to identify both ductile and brittle failures in order to determine the capacity of bolted connection strength. Therefore, there is a need to validate the existing Malaysian Timber Code in order to produce an optimised retrofit design of the wall-diaphragm connections for an unreinforced masonry building in Malaysia, especially the bolted connection on the floor joists or roof rafters. The occurrence of local earthquakes in Malaysia has increased in recent years, thus it is essential to provide sufficient lateral resistance to the unreinforced masonry building due to the absence of connections between the masonry brick walls and timber floor / roof diaphragms in the building as-built constructions. There are many unreinforced masonry buildings in Malaysia, of which, if subjected to earthquake, can cause major devastation and fatality, as most of these buildings are situated in main towns and business district. Because of the lack of bolted connection experimental data on wood species that commonly used to construct roof or floor diaphragms of unreinforced masonry buildings, a series of bolted connection test was conducted. By using the results obtained from this study, the effectiveness of the current timber code was validated and the accuracy of the other design equations such as the European Yield Model (EYM) and the Row Shear Model (RSM) was evaluated. From this experimental study, a calibration factor specifically for Nyatoh hardwood was identified to optimize the bolted connection design using the RSM for the brittle failure mode. To optimize the bolted timber connection design using the EYM for the ductile failure mode, a specific embedding strength value for Nyatoh hardwood was also provided. It was found that the design capacity given by the MS544-5 was too conservative when compared to the EYM and RSM for ductile and brittle failure modes, respectively. From the analyses of results, the 5th percentile bolted connection strength prediction of MS544-5 against the 5th percentile experimental results yielded a percentage accuracy of 27% - 39% for the connections that fail in the ductile mode. A percentage accuracy of 75% - 107% was determined using EYM for the ductile failure mode. In the brittle failure mode, the RSM yielded a percentage accuracy of 50% - 82%, while the MS544-5 generated 32% - 63%.